17-α-Estradiol Has Sex-Specific Effects on Neuroinflammation That Are Partly Reversed by Gonadectomy. Issue 1 (26th July 2021) - Debarba, Lucas K; Jayarathne, Hashan S M; Miller, Richard A; Garratt, Michael; Sadagurski, Marianna
Abstract: 17-α-Estradiol (17aE2) treatment from 4 months of age extends life span in male mice and can reduce neuroinflammatory responses in the hypothalamus of 12-month-old males. Although 17aE2 improves longevity in males, female mice are unaffected, suggesting a sexually dimorphic pattern of life-span regulation. We tested whether the sex-specific effects of 17aE2 on neuroinflammatory responses are affected by gonadal removal and whether hypothalamic changes extend to other brain regions in old age. We show that sex-specific effects of 17aE2 on age-associated gliosis are brain region specific and are partially dependent on gonadectomy. 17aE2 treatment started at 4 months of age protected 25-month-old males from hypothalamic inflammation. Castration before 17aE2 exposure reduced the effect of 17aE2 on hypothalamic astrogliosis in males. In contrast, sex-specific inhibition of microgliosis generated by 17aE2 was not significantly affected by castration. In the hippocampus, gonadectomy influenced the severity of gliosis and the responsiveness to 17aE2 in a region-dependent manner. The male-specific effects of 17aE2 correlate with increases in hypothalamic estrogen receptor alpha expression, specifically in gonadally intact males, consistent with the idea that 17aE2 might act through this receptor. Our results indicate that neuroinflammatory responses to 17aE2 are partially controlled by the presence of sex-specific gonads. Loss of gonadal function and age-associated neuroinflammation could, therefore, influence late-life health and disease onset, leading to sexual dimorphism in both aging and in response to drugs that modify the pace of aging.